Ferroptosis: a key driver and therapeutic target in the pathogenesis of acute respiratory distress syndrome - Yao, Mingjun; Liao, Jinfeng; Liu, Zheng; Zhao, Wei; Song, Siyuan; Huang, Xiaobo; Wang, Yi (Frontiers in Immunology, 2025)
Acute Respiratory Distress Syndrome (ARDS) is a severe inflammatory lung condition often triggered by infections or sepsis, characterized by diffuse alveolar damage, pulmonary edema, and impaired gas exchange. Despite advances in supportive care, ARDS continues to have a high mortality rate. The pathogenesis of ARDS involves an exaggerated immune response leading to tissue damage and inflammation. Regulatory cell death pathways, particularly ferroptosis, an iron-dependent form of cell death driven by lipid peroxidation and oxidative stress, play a critical role in ARDS progression. Ferroptosis is characterized by the accumulation of lipid peroxides and is regulated by enzymes such as glutathione peroxidase 4 (GPX4) and the system Xc- antiporter. Dysregulation of these pathways exacerbates oxidative stress and tissue damage in ARDS. In the context of ARDS, ferroptosis contributes to the destruction of alveolar and endothelial cells, leading to increased vascular permeability, pulmonary edema, and impaired gas exchange. Immune cells like macrophages and neutrophils, while essential for pathogen clearance, can also contribute to lung injury when overactivated, highlighting the need for therapeutic strategies to modulate ferroptosis. Therapeutic targeting of ferroptosis in ARDS includes the use of antioxidants, GPX4 activators, iron chelators, and inhibitors of lipid peroxidation. These approaches aim to reduce oxidative stress, restore antioxidant defenses, and prevent iron-driven cell death. Future research must address challenges in identifying reliable biomarkers, understanding subphenotype-specific mechanisms, and integrating ferroptosis inhibitors into existing therapeutic frameworks. By targeting ferroptosis, it may be possible to mitigate ARDS severity and improve patient outcomes, offering new hope for the management of this devastating condition.